Report on an Enquiry into Conditions of Labour in the Cashewnut Processing Industry in India - Bureau of Ministry of Labour (Bureau of Ministry of Labour, 1953)
The cashewnut tree was introduced into India by the Portughese about 400 years ago. Only in recent years, however, has the cashewnut come into prominence as a commercial crop. The cultivation of cashewnut trees on a commercial basis is of more recent origin and even today the bulk of cashewnuts for processing is obtained from peasants who grow a few cashewnut trees amidst other fruit trees in their small gardens. Cashewnut trees thrive on alluvial soil in the coastal regions and the fact that they could be grown on land unsuitable for usual garden crops augurs well for the extension of cashewnut cultivation on a commercial scale.
Bureau of Ministry of Labour
Bureau of Ministry of Labour